ANALISIS KOMPETENSI SOSIAL GURU DALAM MENURUNKAN RISIKO BURNOUT GURU DI SDN - Pujiastuti, Gunarti Retnoningrum; Yohamintin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Burnout characterized by emotional exhaustion, depersonalization, and decreased work performance, can negatively impact the quality of learning and student well-being. Because there are teachers who still do not understand how social competence specifically helps reduce the risk of burnout in elementary school teachers. However, other teachers seem to be better able to cope with work pressure and remain enthusiastic about their duties. This difference is thought to be closely related to the level of social competence possessed by each teacher. This study aims to (1) analyze the role of social competence in reducing the risk of teacher burnout, (2) identify the forms of burnout experienced by elementary school teachers. The method used is qualitative research with a case study approach. Research shows that improving teachers’ social competence, particularly in communication, empathy, and collaboration, is crucial for preventing and reducing burnout. Despite significant work pressure, teachers who can built positive relationship with students, colleagues, and parent, have greater emotional resilience and are more enthusiastic about their work.